2021
DOI: 10.3390/jfb12030047
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Mechanical Strength of Tissue Engineering Scaffold Due to the Temperature Control of Polymer Blend Solution

Abstract: Polymeric scaffolds made of PCL/PLCL (ratio 1:3, respectively) blends have been developed by using the Thermally Induced Phase Separation (TIPS) process. A new additional technique has been introduced in this study by applying pre-heat treatment to the blend solution before the TIPS process. The main objective of this study is to evaluate the influence of the pre-heat treatment on mechanical properties. The mechanical evaluation showed that the mechanical strength of the scaffolds (including tensile strength, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Besides, a wide OH peak was seen at 3258 cm −1 . Shifting of the bands indicated that there is non‐covalent interaction between TA, TBC, and alginate 33 . Interpenetrating polymer fibers can exert blend characteristics during in vivo and in vitro studies 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, a wide OH peak was seen at 3258 cm −1 . Shifting of the bands indicated that there is non‐covalent interaction between TA, TBC, and alginate 33 . Interpenetrating polymer fibers can exert blend characteristics during in vivo and in vitro studies 34 …”
Section: Resultsmentioning
confidence: 99%
“…Shifting of the bands indicated that there is noncovalent interaction between TA, TBC, and alginate. 33 Interpenetrating polymer fibers can exert blend characteristics during in vivo and in vitro studies. 34 F I G U R E 1 Scanning electron microscopy (SEM) and macroscopic photographs of Alg-nHA (A, B), Alg-TA-nHA (C, D) and Alg-TBC-nHA (E, F) scaffolds.…”
Section: Chemical Characterization Of Scaffoldsmentioning
confidence: 99%
“…Then, Young’s modulus can be obtained from Equation (1). Tensile testing experiments have been carried out to address the mechanical properties of biodegradable cornstarch- [ 112 ], starch/dolomite- [ 113 ] or lignocellulosic- [ 114 , 115 ] based polymers, hydrogels made by carbon dots, hydroxyapatite and polyvinyl acetate [ 116 ] or chitosan-poly (acrylic acid-co-acrylamide) double network [ 117 ], natural-rubber-modified flame-retardant organic montmorillonite [ 118 ] or chlorhexidine-loaded poly (amido amine) [ 119 ] dendrimers, blends consisting of fibrillar polypropylene and polyethylene terephthalate [ 120 ] or poly ε-caprolactone/poly-(lactide-co-ε-caprolactone (PLCL) [ 121 ], polyurethane [ 122 ] and polyethylene [ 123 ] foams, organosilicone elastomer liquid crystals [ 124 ], and skeletal muscle tissues [ 125 ] or PLCL layered sheets with mesenchymal stem cells [ 126 ].…”
Section: Figurementioning
confidence: 99%
“…This prolonged resorption time may interfere with proper bone regeneration within the defect site if a shorter healing period is expected. For this reason, PCL has been successfully copolymerized with hydrogels, like collagen, to augment its resorption kinetics while still providing the scaffold great mechanical strength. , The addition of collagen also improves the scaffold’s osteoconductive properties, which are lessened if PCL is used alone. Furthermore, several composite PCL-mineral scaffolds have been compared to evaluate potential osteointegrative enhancement.…”
Section: Biomaterials For 3d Printed Bony Defect Repair Of the Cmf Sk...mentioning
confidence: 99%